Studying daily fluctuations of emotional effort among nurses of intensive care units: the establishment of latent profiles and its relationship with daily secondary traumatic stress and vitality - Moreno-Jiménez, Jennifer E.; Romero, Miriam; Blanco-Donoso, Luis Manuel; Hernández-Hurtado, Mercedes; Garrosa, Eva (Frontiers in Psychology, 2024)
Nursing professionals working in Intensive Care Units (ICU) face significant challenges that can result in secondary traumatic stress (STS). These challenges stem from witnessing patients' suffering and managing difficult tasks (i.e. communication with patients' relatives). Furthermore, these professionals encounter emotional demands, such as emotional effort, which is the dissonance between the emotion felt and the emotion that should be expressed to meet work expectations. Consequently, we aimed to investigate whether different profiles exist concerning nurses' levels of emotional effort over a five-day period and whether these profiles are related to daily STS and vitality.The sample comprised 44 nursing professionals from ICUs in Spanish hospitals. They were assessed daily, using a package of questionnaires twice per day for five working days: a) immediately after their shift and b) at a later time after working. The findings revealed three distinct profiles based on emotional effort levels: high (Profile 1), moderate (Profile 2), and low (Profile 3). These profiles were found to be negative predictors for both daily shattered assumptions and symptomatology. This study underscores the importance of assessing daily emotional demands in an ICU setting. Such assessments are crucial for establishing preventive measures to help nursing professionals manage lower-level emotional demands.